Propagation and early establishment of red butterfly plant (Cristia vespertilionis) as affected by cutting position, rooting media and shade level - Amjad Farhan bin Ashraf Farhan; Universiti Sultan Zainal Abidin . Faculty of Bioresources and Food Industry (2021)
An enthralling plant species acknowledged as Christia vespertilionis had been
associated with its remarkable capabilities to cure vast range of illnesses, which had
prearranged it to amass prodigious attention from the public nationwide. The overtures
of using Christia vespertilionis as medicinal plants may ascertain to be quite
auspicious, despite the lack of availability for both supply and appropriate technique
for commercialization. The absence of agronomic studies for this plant had
prominently paved to a scarcity in sustainable supply and productivity. Hence, the
objectives of this study were to highlight the plants from its agronomical standpoints
in which to assess the preeminent cutting strata and its propagation media, the
aftermath of the finest growing media as well as to evaluate the superlative shade
requirement for the plant. In the first study, the stock plants were allocated into four
treatments of cutting strata: PI, P2, P3 and P4 whereby PI was the bottommost plant
part while P4 being the uppermost. As for the study of propagation media, plant
cuttings were disseminated amongst cocopeat (CP), burnt rice husk (BRH) and
Holland peat (HP) which comprised of 6 treatments: CP, 3 CP: I BRH, 1 CP: 1 BRH,
1 CP: 3 BRH, BRH and HP. On the other hand, both soil based and soilless media
studies were incorporated as growing media with each consisted of six treatments. The
soil based media had integrated topsoil (TP), sand (SD) and Holland peat (HP): TP, 7
TP: 2 SD, 7 TP: 4 SD, 7 TP: 6 SD, 7 TP: 8 SD and HP whereby the soilless media had
embodied cocopeat (CP), burnt rice husk (BRH) and Holland peat (HP): CP, 3 CP: I
BRH, 1 CP: 1 BRH, 1 CP: 3 BRH, BRH and HP. In terms of shade intensity study,
four treatments were employed: Ll (0%), L2 (50%), L3 (70%) and L4 (90%). In
addition to that, the parameters recorded in this study had comprised of
morphological, physiological and physicochemical data. Throughout the study, it was
highlighted that the preeminent cutting strata and propagation media were the
treatment P3 (third cutting strata) and treatment C4 (1 CP: 3 BRH). Additionally, the
most apposite growing media was soil based media which was treatment T2 (7 TP: 2
SD), whereas the most pertinent shade intensity was established with treatment L4
which had incorporated 90% shade for the plant to proliferate. Last, but not least, the
findings had pointed out that the optimization of abiotic factors such as plant cuttings,
plant media and shade intensity can be translated into better quality and productivity
of C. vespertilionis plants.
1. Introduction -- 2. Literature review -- 3. Methodology -- 4. Results and Discussions -- 5. Conclusion
x
Theses (Degree of Master of Science) - Universiti Sultan Zainal Abidin,2021
Includes bibliographical references (pages 217-273)
Keywords: x; Universiti Sultan Zainal Abidin -- Dissertations; Universiti Sultan Zainal Abidin -- Faculty of Bioresources and Food Industry -- Dissertations; Cristia vespertilionisa; Plants -- Malaysia; on order; Dissertations, Academic